Effects of riparian vegetation removal on the functional feeding group structure of benthic macroinvertebrate assemblages - Ono, E. R. [UNESP]; Manoel, P. S. [UNESP]; Melo, A. L.U. [UNESP]; Uieda, V. S. [UNESP] (Springer Nature, 2020)
The present study aims to verify possible changes in the functional feeding group (FFG) structure of benthic macroinvertebrates related to changes in headwater streams riparian vegetation. Streams with this vegetation fully present (forested), present only on one bank (intermediate) and absent (pasture) were studied. In general, there was low abundance of shredders in all streams, a typical pattern found in neotropical streams. The FFG abundance analysis indicated differences only for the gathering collectors’ group, with the abundance in the forested streams significantly smaller than in the other two profiles. The FFG richness analysis did not indicate significant differences. The RDA analysis made with the environmental and FFG abundance data showed a strong relationship of some habitat characteristics related to environmental quality loss, such as higher values of fine substrate and vegetation on the banks, with the abundance of gathering collectors, filtering collectors and predators in streams with the riparian vegetation partially or totally removed. The initial premise of higher FFG complexity in streams with riparian vegetation was not confirmed. In addition, the results showed a high predators richness, probably favored by the high prey and ambush shelter availability, and the latter represented by vegetal debris and coarse substrate at the forested streams bottom or herbaceous vegetation on the altered streams banks. The functional approach of the present study allowed to verify the advantage of benthic macroinvertebrates use as habitat quality ecological indicators, when analyzed together with environment variables directly or indirectly related to feeding mechanisms.
Keywords: Aquatic insects; Benthic fauna; Bioindicators; Land use; Stream